2021
DOI: 10.1002/jbt.22884
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect ofN‐acetylcysteine against penconazole induced neurodegenerative and neuroinflammatory disorders in rats

Abstract: Penconazole (PEN) is a widely used systemic fungicide to treat various fungal diseases in plants but it leaves residues in crops and food products causing serious environmental and health problems. N-acetylcysteine (NAC) is a precursor of the antioxidant glutathione in the body and exerts prominent antioxidant and antiinflammatory effects. The present study aimed to explore the mechanistic way of NAC to ameliorate the PEN neurotoxicity in male rats. Twenty-eight male rats were randomly divided into four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The results of oxidative stress evaluations reflected on the histopathological picture of liver and kidneys of rats receiving IM and HFM that showing severe pathological alterations related to ROS overproduction. Several studies reported that ROS overproduction increasing cell and mitochondrial membrane permeability and prompts mitochondrial dysfunction disrupting Na/K/ATPase pump causing ionic imbalance (Khalaf et al 2020;Morgan et al 2021) This mechanism explained the observed hepatocellular and renal tubular epithelial cells degeneration in the present Values with different letters are significantly different at P ≤ 0.05 study. Furthermore, oxidative stress causing mitochondrial dysfunction and opining mitochondrial transition pores that increase the cytosolic Ca levels which activate several enzymes leading to protein degradation, lipid peroxidation and DNA damage (Mansour and Mossa 2010).…”
Section: Discussionmentioning
confidence: 47%
“…The results of oxidative stress evaluations reflected on the histopathological picture of liver and kidneys of rats receiving IM and HFM that showing severe pathological alterations related to ROS overproduction. Several studies reported that ROS overproduction increasing cell and mitochondrial membrane permeability and prompts mitochondrial dysfunction disrupting Na/K/ATPase pump causing ionic imbalance (Khalaf et al 2020;Morgan et al 2021) This mechanism explained the observed hepatocellular and renal tubular epithelial cells degeneration in the present Values with different letters are significantly different at P ≤ 0.05 study. Furthermore, oxidative stress causing mitochondrial dysfunction and opining mitochondrial transition pores that increase the cytosolic Ca levels which activate several enzymes leading to protein degradation, lipid peroxidation and DNA damage (Mansour and Mossa 2010).…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, several studies have reported the protective effect of NAC on oxidative stress and apoptosis against various toxins. [58][59][60][61][62][63] NAC can compensate for the adverse effects induced by GLP through its antioxidant and antiapoptotic effects. The antioxidant effect of NAC is attributed to increased levels of glutathione, [23] while the antiapoptotic and cytoprotective impact of NAC is associated with its ability to regulate some apoptosis-and inflammation-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69] Indeed, ginseng aqueous extract ameliorates hepatorenal toxicity caused by an insecticide in rats. 70 Moreover, N-acetylcysteine, a precursor molecule of reduced GSH, the most important endogenous antioxidant molecule, acts protectively against penconazole-induced neurodegenerative and neuroinflammatory disorders in rats, 71 lupeol protects against mancozeb-induced genotoxicity in human lymphocytes 72 and ascorbic acid supplementation is effective against cytotoxicity and DNA fragmentation induced by triphenyltin on human liver carcinoma cells. 73 In addition, manganese supresses oxidative stress, inflammation and caspase-3 activation in rats exposed to chlorpyrifos 74 and VA protects against benomylinduced oxidative stress and apoptosis in neural cells.…”
Section: Discussionmentioning
confidence: 99%